New Directions in Surveillance and Privacy (willan Publishing, 2009)
The field of surveillance studies is developing at a rapid rate, fuelled by a deep unease about the future of individual privacy and growing interest in a number of questions that lie at the heart of the discipline. What information is held about us? To what extent is that information secure? How should new technologies be regulated? How will developments in surveillance affect our ordinary and everyday lives? Deliberately multi-disciplinary in character, New Directions in Surveillance and Privacy examines these questions from a range of different perspectives, and includes contributions from leading academics in sociology, law, management studies, literary analysis and Internet studies. As privacy comes under increasing threat and surveillance extends into more and more areas of our daily lives, surveillance studies needs to develop in new directions, form new perspectives, and gain new insights. In keeping with this aim, the chapters of this book consider how individuals, organisations, and states gather, analyse, and share ever-increasing amounts of our personal and private information. Divided into three sections, this book contains chapters touching on issues of legal regulation, changes in the technology of surveillance, and on the future of privacy and surveillance. In so doing, this new collection provides a unique and eclectic insight into the question of how the spread of surveillance is changing our lives and the societies in which we live.